2017
DOI: 10.1074/jbc.m117.775460
|View full text |Cite
|
Sign up to set email alerts
|

Inositol Depletion Induced by Acute Treatment of the Bipolar Disorder Drug Valproate Increases Levels of Phytosphingosine

Abstract: Bipolar disorder (BD) is a severe psychiatric illness affecting ∼1% of the world population. Valproate (VPA) and lithium, widely used for the treatment of BD, are not universally effective. These drugs have been shown to cause inositol depletion, but translating this observation to a specific therapeutic mechanism has been difficult, hampering the development of more effective therapies. We have shown previously in yeast that chronic VPA treatment induces the unfolded protein response due to increasing ceramid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Recently, Jadhav and collaborators have shown that treatment of yeast cells with valproate (VPA), a widely used drugs to treat bipolar disorder (BD), increases the levels of PhytoSO via de novo synthesis and at the same time leading to inositol depletion and upregulation of unfolded protein response [206]. They further demonstrated that VPA mediated increase in SL de novo synthesis is due to a downregulation of Orm1/2 expression, and upregulation of expression of fatty acid elongases Sur4 and Fen1, as well as of genes involved in the export and metabolism of PhytoSO [206,207]. Since, VPA induced inositol depletion is also observed in mammalian cell models [208,209] these findings suggest that inositol depletion and the consequent increase in PhytoSO levels might underlie the therapeutic action of VPA [207], which is promising for the development of new therapeutic approaches for BD treatment.…”
Section: Role In Diseasementioning
confidence: 99%
“…Recently, Jadhav and collaborators have shown that treatment of yeast cells with valproate (VPA), a widely used drugs to treat bipolar disorder (BD), increases the levels of PhytoSO via de novo synthesis and at the same time leading to inositol depletion and upregulation of unfolded protein response [206]. They further demonstrated that VPA mediated increase in SL de novo synthesis is due to a downregulation of Orm1/2 expression, and upregulation of expression of fatty acid elongases Sur4 and Fen1, as well as of genes involved in the export and metabolism of PhytoSO [206,207]. Since, VPA induced inositol depletion is also observed in mammalian cell models [208,209] these findings suggest that inositol depletion and the consequent increase in PhytoSO levels might underlie the therapeutic action of VPA [207], which is promising for the development of new therapeutic approaches for BD treatment.…”
Section: Role In Diseasementioning
confidence: 99%
“…They further demonstrated that VPA mediated increase in SL de novo synthesis is due to a downregulation of Orm1/2 expression, and upregulation of expression of fatty acid elongases Sur4 and Fen1, as well as of genes involved in the export and metabolism of PhytoSO [206,207]. Since, VPA induced inositol depletion is also observed in mammalian cell models [208,209] these findings suggest that inositol depletion and the consequent increase in PhytoSO levels might underlie the therapeutic action of VPA [207], which is promising for the development of new therapeutic approaches for BD treatment.…”
Section: Role In Diseasementioning
confidence: 96%
“…J o u r n a l P r e -p r o o f inhibition-A previously reported microarray analysis of the yeast gene expression response to VPA suggested altered expression of metabolic genes (28). qPCR analysis indicated no change in SUC2 (invertase; sucrose metabolism) expression and increased expression of POX1 (fatty-acyl CoA oxidase; β-oxidation), CIT2 and MLS1 (citrate synthase 2 and malate synthase; glyoxylate cycle), PCK1 (phosphoenolpyruvate carboxykinase; gluconeogenesis), and CAT2 (carnitine acetyl-CoA transferase; carnitine shuttle) in response to VPA treatment (1 mM, 30 min) (Fig.…”
Section: Vpa Activates Snf1 Independent Of Inositol Depletion and Cytochrome C Oxidasementioning
confidence: 99%
“…Cross-species functionality has been demonstrated from yeast to mammalian cells, and the yeast model has been pivotal in identifying mammalian upstream activating kinases (27). Interestingly, a microarray analysis J o u r n a l P r e -p r o o f conducted to identify pathways affected by VPA in yeast revealed a pattern of altered expression of metabolic genes that is similar to the pattern observed during Snf1 activation (28,29). In the current study, we further exploited the yeast model to gain insight into the mechanism of activation of SNF1/AMPK by VPA.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation